Avaliação da metodologia de sequenciamento direto de blocos aplicada em depósitos de minério de ferro - Hudson Rodrigues Burgarelli (2017)
This study aims to evaluate the applicability of Direct Block Scheduling methodology in iron ore deposits. Three case studies in real deposits were conducted, comparing the Direct Blok Scheduling with the conventional mine planning method, which uses the Lerchs-Grossmann algorithm. Direct Blok Scheduling applies a unique optimization process that encompasses all stages developed in the classical methodology, taking into account the geological uncertainty in the generation of the mine plan. In the case studies, we made use of two geological deposits represented by a estimated model and a deposit representing both by a estimated and by a simulated model. The objective is to evaluate the advantages of this new methodology, taking into account the characteristics of each deposit. The results indicate that, applying the Direct Block Scheduling methodology, it is possible to obtain mining sequences with higher net present value, increasing the project value, even in deposits represented by deterministic models. This increase is due to the capabilities of this methodology to correctly apply the discount factor, which allows the decision to mine the block to be evaluated according to the period in which the block will be mined. This causes the material mined in later periods to be penalized with a larger discount factor, as expected in reality. In this way, the system tends to mine the material that will generate a higher revenue in the first periods, even if in some cases this also slightly increases the amount of waste mined, but that result in a higher value of the project. This increase in the project value is related to the grade heterogeneity of the deposit, so deposits that are more heterogeneous tend to present greater gains. In addition, when using simulated models, it is possible to evaluate the risks associated with the defined mining sequence, in order to minimize these risks in the first periods of the project